যত দূর মনে পড়ে : রাজনৈতিক আত্নকথন - বসু, জ্যোতি, ১৯১৪-২০১০. (কলকাতা : ন্যাশনাল বুক এজেন্সি, 2006)
Political autobiography of chief minister and a Marxist leader of West Bengal.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Basu, Jyoti, -- 1914-2010.; Politicians -- India -- West Bengal -- Biography; Communists -- India -- West Bengal -- Biography; West Bengal (India) -- Politics and government; West Bengal (India) -- Biography